Legal Reconstruction of Employee Shareholder Protection through ESOP Program from Termination of Employment - Musimin, Suyono; Iriantoro, Agung (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Article 43, paragraph 3 of Law Number 40 of 2007 concerning Limited Liability Companies allows an employee to become a shareholder of the company through the ESOP (Employee Stock Option Program). In practice, an ESOP by companies is stated in a stock option agreement that outlines the rights and obligations of employees concerning the stock options. The position of employees will certainly not be exempt from the HR management policies carried out by the company, including the Termination of Employment policy. Compensation as an employee's right when Termination of Employment occurs is Severance Pay, Long Service Award Pay, Replacement of Rights, and Separation Pay if entitled only to Separation Pay. This study aims to examine and find forms of legal protection and find weaknesses in legal protection for employee shareholders (ESOP) when laid off, and to find efforts to reconstruct legal protection for employee shareholders (ESOP) when laid off. This research is normative juridical. Using secondary data as the primary source, the research was conducted through document studies via library research, employing both statistical and conceptual approaches. The results of this study are: first, that the legal provisions regarding layoffs of employees who are also shareholders of the company through ESOPs in Government Regulation Number 35 of 2021 concerning Fixed-Term Employment Agreements, Outsourcing, Working Hours and Rest Periods, and Termination of Employment have not been able to provide maximum legal protection for the rights of employees who are also shareholders. The current reality is that when ESOP employees are laid off, the company only relies on their employee status, the reason for the layoff, and the rights clearly stated in the legislation. Second, the research findings indicate that the reconstitution of Article 40 paragraph 4 letter (c) of Government Regulation 35 of 2021 aims to provide certainty and legal protection for ESOP employees in the event of layoffs by the company.